The supportive state families, government, and America's political ideals - Eichner, Maxine (New York ; Oxford : Oxford University Press, 2010)
There is broad agreement among politicians & policymakers that the family is a critical institution of American life. Yet the role that the state should play with respect to family ties among citizens remains deeply contested. This controversy over the state's role underlies a broad range of public policy debates.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Family policy -- United States; Families -- United States